ANTIBACTERIAL ACTIVITY OF FRACTIONS OF ETHYL ACETATE EXTRACT OF GARCINIA LATTISSIMA MIQ. FRUITS - Ambarwati, NENENG SITI SILFI; Malik, Amarila; Listari, Ageng Tri; Nirwana,; Elya, Berna; Hanafi, Muhammad (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objectives: The emergence of new infections and increase in bacterial drug resistance has created a serious need for the expansion of new antibacterial agents from natural sources. The study was carried out to evaluate the antibacterial activity of fractions of ethyl acetate extract of Garcinia latissima Miq. fruits. Methods: The fractionation was done using a silica gel column and organic solvents as the eluent, i.e., n-hexane, ethyl acetate, and methanol. All fractions were assayed for antibacterial activity, which was done by performing disc diffusion for growth inhibition against Bacillus subtilis and Pseudomonas aeruginosa. In addition, the growth inhibition activity was also examined by performing bioautography assay using pre-coated silica gel 60 GF 254 plates as the stationary phase. Fractions A-F were eluted using n-hexane:chloroform (1:4), while Fractions G-K were used ethyl acetate:dichloromethane (4:1) as the mobile phase. The plate was visualized by ultraviolet at Î» 254 nm and 366 nm, while the other one was contacted with the inoculated agar medium to observe zone inhibition. Further, the minimum inhibitory concentration (MIC) value was determined by performing microdilution. Results: The result showed that the antibacterial activity of all fractions was more active at inhibiting the growth of B. subtilis than P. aeruginosa, mainly for Fractions H and J. However, the strongest antibacterial activity was showed by Fractions H and J against B. subtilis, MIC 312.5 Î¼g/mL (lower than reference, which is erythromycin antibiotic (25 Î¼g/mL), followed by Fraction D against B. subtilis MIC 625 Î¼g/mL, Fraction K against P. aeruginosa MIC 625 Î¼g/mL, whereas Fractions C, E, and G against B. subtilis, and Fraction E against P. aeruginosa also showed low MIC values (1.250 Î¼g/mL). Conclusions: The results indicated that fractions of G. latissima Miq. fruit ethyl acetate extracts possessed antibacterial activity. The most active fraction that inhibited the growth of B. subtilis was shown by Fractions H and J; these fractions have the potential to be developed as new antibacterial agents.